ANALYSIS OF THE INTRINSIC ELEMENTS OF A SHORT STORY “LELAKI YANG TUBUHNYA HABIS DIMAKAN IKAN-IKAN KECIL” BY MASHDAR ZAINAL - Duril, Sefrury; Khaerunaila, Muh. Fajar; Kezia, Triadinda Cias; Putra, La Ode; Mutmainnah, Mutmainnah (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2024)
Short story is a part of literary genres, which is a fiction, that most of it relies on fantasy stories such as fairy tale. Short stories have elements that are divided into two which are intrinsic elements and extrinsic elements. This study aims to analyse the intrinsic elements in the short story titled